Balanced steady-state free precession MRCP is a robust alternative to respiration-navigated 3D turbo-spin-echo MRCP - Hasse, Felix; Selmi, Buket; Albusaidi, Hamed; Mokry, Theresa; Mayer, Philipp; Rupp, Christian; Kauczor, Hans-Ulrich; Weber, Tim (BMC medical imaging, 2021)
Despite synchronization to respiration, respiration-navigated (RN) 3D turbo-spin-echo MRCP is limited by susceptibility to motion artifacts. The aim of this study was to assess the quality of pancreaticobiliary duct visualization of a non-RN MRCP alternative based on balanced steady-state free precession imaging (BSSFP) with overlapping slices compared with RN-MRCP.
Gesehen am 05.02.2021